Evaluation of Proton Pump Inhibitors Prescribing among Non-Critically Ill Hospitalized Patients in a Malaysian Tertiary Hospital - Mohamed Hassan Elnaem,Mohamad Haniki Nik Mohamed,Amirul Hazim bin Nazar,Rabiatul Nur Khaliesa binti Ibrahim (Journal of Applied Pharmaceutical Science, 2017)
Background: There are raised concerns regarding the rational guidelines-based prescribing of proton pump inhibitors (PPIs) therapy in the hospital setting. Objective: To describe the current prescribing practice of PPIs among hospitalized patients in non-intensive care settings. Also, the study aimed to evaluate the appropriateness of the prescribed PPIs. Methods: A cross-sectional study was conducted in the medical ward of a tertiary hospital in the state of Pahang, Malaysia. A total of 153 medical records of non-critically-ill adult patients receiving PPI therapy were investigated. The assessment of PPI prescribing was performed referring to clinical guidelines and the list of PPI-approved indications. Results: The most frequently prescribed PPI regimen has been pantoprazole 40 mg OD. Approximately 34% of the prescribed regimens were considered to be appropriate as it was consistent with the clinical guidelines. However, about 31% of the prescribed PPIs did not have a clear indication. Moreover, the inappropriate use of PPIs was revealed in nearly 19% of the total PPIs prescriptions. Finally, 16% of the prescribed PPIs were in need of dosage adjustment due to the presence of drug-drug interactions with the concurrently used medications. Conclusion: Inappropriately prescribed PPIs are prevalent among non-critically ill-hospitalized adult patients in a Malaysian tertiary hospital. Initiatives for enforcing rational prescribing should focus on the proper documentation of evidence-based indications of PPIs in the medical records. There is a desperate need in the local setting for well-defined PPIs prescribing criteria. Future research should design and examine the impact of prescribing improvement interventions on the PPIs rational prescribing.
Keywords: Proton pump inhibitors,Malaysia,prescribing patterns,Clinical practice guidelines,evaluation.